2021
DOI: 10.2151/sola.2021-026
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Frequency and Intensity of Dust Events Crossing the Mongolia–China Border

Abstract: This is a PDF of a manuscript that has been peer-reviewed and accepted for publication. As the article has not yet been formatted, copy edited or proofread, the final published version may be different from the early online release.This pre-publication manuscript may be downloaded, distributed and used under the provisions of the Creative Commons Attribution 4.0 International (CC BY 4.0) license. It may be cited using the DOI below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Based on data from 1980 to 2005, Zhang and Gao [19] found there were mainly three potential dust sources affecting northern China, and approximately 70% of the DS events impacting China originated from Mongolia. Bao et al [20] investigated the spatiotemporal variations of border-crossing dust events between Mongolia and Inner Mongolia and supported the results that the sand and dust from Mongolia play a major contribution to the DS events in China. Previous investigations have been conducted on the vertical structure during the dust period in arid and semiarid areas of China.…”
Section: Introductionmentioning
confidence: 80%
“…Based on data from 1980 to 2005, Zhang and Gao [19] found there were mainly three potential dust sources affecting northern China, and approximately 70% of the DS events impacting China originated from Mongolia. Bao et al [20] investigated the spatiotemporal variations of border-crossing dust events between Mongolia and Inner Mongolia and supported the results that the sand and dust from Mongolia play a major contribution to the DS events in China. Previous investigations have been conducted on the vertical structure during the dust period in arid and semiarid areas of China.…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, China has been severely affected by SDSs. Studies have shown that the majority of the SDSs affecting China originate from Mongolia [5][6][7]. Bao et al [6] reported that, during 1977−2018, approximately 50% of the total spring dust days in China were attributable to cross-border SDSs originating from Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the majority of the SDSs affecting China originate from Mongolia [5][6][7]. Bao et al [6] reported that, during 1977−2018, approximately 50% of the total spring dust days in China were attributable to cross-border SDSs originating from Mongolia. In particular, in recent years, cross-border SDSs between Mongolia and China have occurred frequently, and their severe impacts on Northern China have attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…With the ensuing global climate change, extreme weather events are becoming more frequent [19,20]. Several studies have shown that both grassland fires and dust weather have increased in Mongolia recently [8,21,22]. Therefore, it is crucial to investigate whether grassland fires affect dust weather and the potential underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%